2018
DOI: 10.1111/pai.12957
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial hyper‐responsiveness in preterm‐born subjects: A systematic review and meta‐analysis

Abstract: Preterm-born subjects especially those who had CLD had increased rates of BHR to direct (methacholine) and indirect (exercise) stimuli compared to term-born subjects suggesting subgroups might benefit from anti-inflammatory or bronchodilator therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 44 publications
1
24
0
2
Order By: Relevance
“…Several studies have shown evidence of persistent abnormal lung function in later childhood for infants diagnosed with CLD. In previous systematic reviews, we have reported that preterm‐born subjects have deficits in FEV 1 , increased rates of bronchial hyper‐responsiveness, and single doses of bronchodilators appeared to improve FEV 1 . It has been reported that preterm‐born subjects have higher rates of wheezing and are often diagnosed with asthma.…”
Section: Introductionmentioning
confidence: 89%
“…Several studies have shown evidence of persistent abnormal lung function in later childhood for infants diagnosed with CLD. In previous systematic reviews, we have reported that preterm‐born subjects have deficits in FEV 1 , increased rates of bronchial hyper‐responsiveness, and single doses of bronchodilators appeared to improve FEV 1 . It has been reported that preterm‐born subjects have higher rates of wheezing and are often diagnosed with asthma.…”
Section: Introductionmentioning
confidence: 89%
“…The mechanisms of ASM contractility have been well studied in adults, 9,10 but are relatively less known in developing airways. Nonetheless, using isolated ASM cells from lungs of [18][19][20][21][22] week fetuses, we have demonstrate their suitability for studying regulation of [Ca 2+ ] i and proliferation, 11 showing that fASM cells express [Ca 2+ ] i regulatory proteins and respond to bronchoconstrictor agonists such as acetylcholine (ACh) and histamine with robust [Ca 2+ ] i responses. Using this model, we previously found that O 2 enhances fASM [Ca 2+ ] i 11 as well as cellular contractility, 12 and O 2induced increases in airway contractility have also been observed in neonatal mouse models of hyperoxia.…”
Section: Introductionmentioning
confidence: 89%
“…58 A comprehensive systematic review and meta-analysis has recently reviewed bronchial hyperresponsiveness (BHR) in preterm-born subjects. 59 Bronchial provocation tests to methacholine and exercise indicated that preterm-born individuals had greater BHR compared with term-born, particularly those with chronic lung disease.…”
Section: Pred Ic Ti On and Pre Venti On Of Allerg I C D Is E A S Ementioning
confidence: 99%